Security on Charity Crowdfunding Services using KAMI Index 4.1 - Tawar; Imam Riadi; Ariqah Adliana Siregar; Adiniah Gustika Pratiwi (Engineering Science Letter, 2022)
Technological developments are multiplying. The ABC charity currently has a crowdfunding service. This service helps simplify the user management process. Security is a crucial issue to support and guarantee funders. This research aims to evaluate and provide recommendations for crowdfunding services to run safely and smoothly using the KAMI Index 4.1. This research consists of several steps, starting with observations made at charitable institutions. The following process is through focus group discussion activities to assess the level of information security of crowdfunding services. The analysis of the calculation results is used as the basis for developing recommendations. Based on the assessment results, crowdfunding services at charities obtained scores of I to I+, this indicates that the charity is still in its initial condition and has not yet implemented information security standards in managing crowdfunding services. Recommendations proposed to increase the value are carried out by compiling and implementing information security at the charity.